Negotiating Femininity and Masculinity: A Judith Butler Approach to Megan Trainor’s 'Dear Future Husband' - Ria Saraswati (Proceeding of the International Conference on Global Education and Learning, 2024)
This study employs Judith Butler’s theory of gender performativity to analyze Megan Trainor’s song "Dear Future Husband," exploring the negotiation of femininity and masculinity within contemporary pop culture. Utilizing a qualitative content analysis method, the research examines lyrical content, musical elements, and visual representations associated with the song to uncover underlying gender norms and performances. The results reveal that "Dear Future Husband" both reinforces and subverts traditional gender roles; while it portrays conventional expectations of femininity and masculinity, it simultaneously introduces nuanced demands for mutual respect and partnership. The discussion highlights the complexity of gender performances in mainstream media, suggesting that Trainor’s work reflects a transitional phase in societal understandings of gender dynamics. By applying Butler’s framework, the study illustrates how pop songs can serve as sites for both perpetuating and challenging normative gender constructs, offering insights into the evolving landscape of gender identity and expression.